A Biodegradable Coating Based on Self‐Assembled Hybrid Nanoparticles to Control the Performance of Magnesium. Issue 19 (3rd September 2015) - Sun, Jiadi; Zhu, Ye; Meng, Long; Shi, Tiantian; Liu, Xiaoya; Zheng, Yufeng
<x xml:space="preserve">Abstract</x> A new biodegradable nanocomposite coating to control the biocompatibility and anticorrosion property of Mg is reported in this work. The key feature of this strategy is to equip the Mg surfaces with poly(γ‐glutamic acid)‐g‐7‐amino‐4‐methylcoumarin/hydroxyapatite (γ‐PGA‐g‐AMC/HA) hybrid nanoparticles via electrophoretic deposition in ethanol. The microstructures of the resulting nanocomposite coating are characterized by Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscopy. The results of standard electrochemical measurements along with immersion tests indicate that the nanocomposite coating has preferable in vitro degradation and corrosion resistance behavior than bare Mg. In addition, cytocompatibility is conducted using NIH3T3 cells and the coated sample shows better cell viability and cell adhesion than pure Mg substrate over the whole incubation period. The favorable anticorrosion behavior and cytocompatibility of the nanocomposite coating suggest that the newly developed γ‐PGA‐g‐AMC/HA biodegradable nanocomposite coating may have a potential to improve the biological performance of Mg‐based biomedical implants.